Bacillus velezensis HN-2: a potent antiviral agent against pepper veinal mottle virus - Xuan, Zhe; Wang, Yu; Shen, Yuying; Pan, Xiao; Wang, Jiatong; Liu, Wenbo; Miao, Weiguo; Jin, Pengfei (Frontiers in Plant Science, 2024)
Pepper veinal mottle virus (PVMV) belongs to the genus Potyvirus within the family Potyviridae and is a major threat to pepper production, causing reduction in yield and fruit quality; however, efficient pesticides and chemical treatments for plant protection against viral infections are lacking. Hence, there is a critical need for discovering highly active and environment-friendly antiviral agents derived from natural sources. Bacillus spp. are widely utilized as biocontrol agents for managing fungal, bacterial, and viral plant diseases. Particularly, Bacillus velezensis HN-2 exhibits a strong antibiotic activity against plant pathogens and can also induce plant resistance. In this study, we assessed the antiviral properties of Bacillus velezensis HN-2 and its chemical counterparts. The results of bioassays revealed the robust colonization capability of Bacillus velezensis HN-2, particularly in intercellular spaces, leading to delayed infection and enhanced protection against PVMV through multiple plant defense mechanisms, thereby promoting plant growth. Furthermore, Bacillus velezensis HN-2 increased the activities of antioxidant enzymes, thereby mitigating the PVMV-induced ROS production in Nicotiana benthamiana. Moreover, the application of Bacillus velezensis HN-2 at 5 dpi significantly increased the expression of JA-responsive genes, whereas the expression of salicylic acid-responsive genes remained unchanged, implying the activation of the Ja signaling pathway as a crucial mechanism underlying Bacillus velezensis HN-2-induced anti-PVMV activity. Immunoblot analysis revealed that HN-2 treatment delayed PVMV infection at 15 dpi, further highlighting its role in inducing plant resistance and promoting growth and development. These findings underscore the potential of Bacillus velezensis HN-2 for field application in managing viral plant diseases effectively.